Teknik Desensitisasi Sistematik untuk Mengurangi Fobia Mahasiswa - Firosad, Ahmad Masrur; Nirwana, Herman; Syahniar, Syahniar (Universitas Negeri Padang, 2016)
People do many things to reach effective life and stay away from trouble. One of indicators which disturb life is worrying too much about something irrational such as phobia. Phobia can be omitted by systematic desensitizationÂ technique. Systematic desensitizationÂ technique is one of techniques for counseling to reduce scary emotional response or something worrying through activities which are contrary to those responses. This research aims to (1) description phobia condition before treatment (pretest) and after treatment (posttest), (2) examine effectively systematic desensitization technique to reduce phobia of students.This research uses quantitative research method, type of this research is a kind of quasi experiment. This design uses pretest posttest one group design, there is an experiment group over here. Technique for collecting subject is non random sampling, selection for subjects based on certain considerations and adjusted to research purposes, there are 8 students of Tarbiyah and Education Faculty IAIN Imam Bonjol Padang suffering phobia. Instrument used is questionnaire with 0,851 of total validity and 0,923 of reliability. Data is analyzed using wilcoxon statistic test.Discovery of this research shows that: (1) systematic desensitization technique effectively heals phobia of students, (2) there are differences between pretest and posttest phobia condition.